2019
DOI: 10.3390/medicina55010010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Turmeric Nanoparticles as Anti-Gout Agent: Modernization of a Traditional Drug

Abstract: Background and objectives: Turmeric has assisted in the control of inflammation and pain for decades and has been used in combination with other nutraceuticals to treat acute and chronic osteoarthritis pain. Recently, the effect of turmeric, turmeric extract, or curcuminoids on musculoskeletal pain, either by themselves or in conjunction with other substances, has been reported. The aim of this study was to develop and characterize turmeric nanoparticles (T-NPs) for various parameters, both in vitro and in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…SNEDDS have shown excellent potential to enhance the oral bioavailability of highly lipophilic drugs [21]. Ex vivo permeation studies can mimic the potential improvement in drug permeability once inside the GIT [10]. The results of ex vivo permeation revealed a 3.2-fold increased permeation with LCT 14 across the rat intestine as compared to other formulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SNEDDS have shown excellent potential to enhance the oral bioavailability of highly lipophilic drugs [21]. Ex vivo permeation studies can mimic the potential improvement in drug permeability once inside the GIT [10]. The results of ex vivo permeation revealed a 3.2-fold increased permeation with LCT 14 across the rat intestine as compared to other formulations.…”
Section: Discussionmentioning
confidence: 99%
“…The most popular nano-based strategies for lipophilic drugs include incorporation of drugs in lipid vehicles like oil/surfactant dispersion [5], micro and nanoemulsions [6,7], and self emulsifying drug delivery systems. Self-nanoemulsifying drug delivery systems (SNEDDS) have emerged as a vital strategy for the efficient delivery of drugs with poor aqueous solubility [8,9,10]. SNEDDS are well known for their potential to enhance the solubility and absorption of the lipophilic drugs [11] by increasing the surface area and decreasing the size of oil droplets that are readily digestible and incorporated into mixed micelles that can pass the intestinal lumen [12].…”
Section: Introductionmentioning
confidence: 99%
“…These study findings clearly demonstrate the influence of oil and surfactant on the ingression of constricted junctions and facilitation of the ACV transport through transcellular routes across the stratum corneum. It could be anticipated that the SNEDDS components contributed substantially in expediting the evasion of ACV through both the lipid structures of the interlamellar region and corneocytes with their keratin-enriched matrix of the skin’s transcellular routes [ 36 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Study done by Mustafa Kiyani M et al showed that; Uric acid concentrations were considerably decreased after treatment with turmeric nanoparticles (T-NPs), signifying that T-NPs show higher potential against gout control [10].…”
Section: Fig 1 Shows Organic Cinnamonmentioning
confidence: 99%